2007
DOI: 10.1080/00207140600995745
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotizability and Somatic Complaints:A Gender-Specific Phenomenon

Abstract: Abstract:The relationship between hypnotizability and somatic illness was measured in 45 college students. Several weeks after completing the Waterloo-Stanford Group C Scale (WSGC), participants filled out a somatic-complaint checklist and measures of psychopathology. Results indicated a positive correlation between hypnotizability and somatic illness, and the relationship was stronger for female participants. In contrast to the quadratic model proposed by Wickramasekera, the current data demonstrated a linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…What was notable was that imagery predicted response to treatment, and there is some evidence that individuals with higher hypnotizability scores are more susceptible to certain illnesses such as posttraumatic stress disorder, which also responds well to hypnosis (Brown, 1918;Spiegel, Hunt, & Dondershine, 1988). Furthermore, we have shown that imagery is also related to noncolonic symptomatology, which is consistent with a report that individuals with high hypnotizability scores are more likely to suffer from somatic complaints (Younger et al, 2007). Thus, traits that contribute to hypnotizability may actually predispose to the very disorders that respond well to hypnosis, and it is tempting to speculate that this might also apply to IBS.…”
Section: Discussionsupporting
confidence: 68%
“…What was notable was that imagery predicted response to treatment, and there is some evidence that individuals with higher hypnotizability scores are more susceptible to certain illnesses such as posttraumatic stress disorder, which also responds well to hypnosis (Brown, 1918;Spiegel, Hunt, & Dondershine, 1988). Furthermore, we have shown that imagery is also related to noncolonic symptomatology, which is consistent with a report that individuals with high hypnotizability scores are more likely to suffer from somatic complaints (Younger et al, 2007). Thus, traits that contribute to hypnotizability may actually predispose to the very disorders that respond well to hypnosis, and it is tempting to speculate that this might also apply to IBS.…”
Section: Discussionsupporting
confidence: 68%
“…Our results on left insular and cerebellar lobule IV peculiarities of highs totally fit with the findings by Ebisch and colleagues [59], suggesting that the changes of these brain structures could represent the correlate of the altered emotional processing reported in highs. In fact, higher emotional intensity during internal imagery [60], sensitivity and empathy [15], tendency to somatic complaints [61], and vividness of pain imagery [46] have been reported in highs. Furthermore, an fMRI study on a sample of highs revealed common activations of the left insula and left cerebellum, besides prefrontal and parietal cortices, during both hypnotically and physically [62].…”
Section: Cerebellummentioning
confidence: 99%
“…Present findings do not allow to exclude that med-highs may exhibit a different association between ABP, PETCO2 and cerebral blood flow with respect to med-lows also when ABP increases. In this respect, it may be interesting that more frequent increases in systemic blood pressure are likely to occur in highs than in lows owing to their greater emotional intensity, empathy [69,70] and interoceptive sensitivity [12,69]. In addition, changes in synaptic glutamate due to tasks could induce increases in the astrocyte's calcium mediated dilatory action independently from systemic blood pressure [71].…”
Section: Limitations and Conclusionmentioning
confidence: 99%